A SCALE DEVELOPMENT STUDY ON MOTIVATION SOURCES OF SPORT SCIENCES GRADUATES IN FOREIGN LANGUAGE LEARNING - Yücel, Ali Serdar; Aras, Gökşen; Korkmaz, Murat (METİN YAMAN, 2023)
Introduction: The motivational challenges faced by sport science graduates in foreign language learning are one of the focal points of research in this field. Foreign language learning is an important factor for sports science graduates. Because sport is an international field and requires communication, language skills are needed. However, lack of motivation affects the language learning process. Lack of motivation is an obstacle that sport sciences graduates face in foreign language learning. This situation leads to problems such as inattention, apathy and low level of success. The reasons for lack of motivation include difficulties in adapting to the requirements of language learning, lack of belief in language learning skills, lack of extrinsic motivation and difficulties in the language learning process. This is among the findings that sport science graduates are highly demotivated by the lack of knowledge to understand the advantages of language learning in their sport careers. Results: A supportive learning environment for sport sciences graduates should be provided and students are not given the opportunity to observe their progress in the language learning process. It is also among the results that the variety of learning materials and activities to increase motivation and the factors for interesting and interactive activities are not formed. It is among the results of the research that interactive methods that encourage active participation in language learning are not used. It is seen that participants in academic life do not work with real-life examples to improve their language skills. In addition, methods such as setting goals and tracking progress are not used by the participants for motivational purposes. Conclusion: It is a common problem that sport science graduates face a lack of motivation in foreign language learning. Various approaches such as awareness-raising activities, a supportive learning environment and interactive teaching strategies should be used to overcome this challenge. Increasing sport science graduates' motivation to learn a language has been shown to be a crucial factor for improving their language skills and expanding opportunities in their sport careers.
Keywords: Sociology of Sports; Spor Sosyolojisi